Economic fluctuations and growth in sub-saharan Africa: the importance of import instability - Fosu, Augustin Kwasi (2001)
The traditional thesis that export instability (XI) is deleterious to economic growth in developing economies has received mixed empirical results. For African countries, recent reseach suggests that the effect of XI is weak, but that capital (investment) instability (K1) adversely influences economic growth. The current study argues that in many of these nations, imports are likely to be critical to the growth process, while exports represent only one of the various sources of investment resources. Hence, import instability (MI) may pose a more serious problem that X in hindering economic growth. Employing 1968-86 World Bank data for 33 sub-Saharan Afican countries, XI, K1 and MI variables are calculated for each country as the standard errors around the respective `best-fitted' trends over the sample period. These instability measures and additional Wold Bank data are then used to estimate an augmented production function that controls for the effects of labour, capital, and exports. The study finds that although K1 is still a relevant argument of the production function, M1 appears to be even more important, while X1 is extraneous. - Reproduced.
Keywords: Economic growth - Africa; Economic growth